Understanding the Influence of Collaborative Tasks on User Experience in Moodle - Azevedo, Romualdo; Lucena, Ketlen; Castro, Alberto; Gadelha, Bruno (Journal of the Brazilian Computer Society, 2026)
Learning Management Systems (LMSs) are widely adopted to support teaching and learning across diverse contexts, including higher education, corporate training, professional certification, and hybrid or fully online courses. These platforms enable flexible access to resources, asynchronous interactions, and integration of individual and collaborative learning activities. While numerous studies have assessed LMS usability and features, the specific influence of collaborative activities on user experience (UX) remains underexplored. This study investigates how collaboration affects UX in Moodle by comparing individual and peer review–based collaborative activities. We conducted a case study with 35 undergraduate Software Engineering students, following Wohlin’s five-step methodology: scope definition, planning, operation, analysis, and presentation. Participants completed an individual task and a collaborative Peer Review activity, after which UX was evaluated through the Attrakdiff questionnaire and Focus Group discussions. Quantitative results indicated notable differences between individual and collaborative contexts, with collaborative activities perceived as more inventive, stimulating, and pleasant, though issues such as lack of interaction, unclear learnability, and system constraints impacted satisfaction. Qualitative analysis revealed that course structure, the configuration of collaborative activities, and specific Moodle features—such as notifications, feedback mechanisms, and progress tracking—strongly shape UX. Contributions include: (i) empirical evidence of how collaboration-related aspects influence LMS UX; (ii) a replicable methodology combining quantitative and qualitative UX evaluations; (iii) actionable recommendations for improving Moodle’s support of collaborative learning, enhancing engagement and learning outcomes; and (iv) we list a set of recommendations for professors to configure Peer Review in Moodle.